Prevalência sorológica e molecular de Babesia bovis e Babesia bigemina em búfalos (Bubalus bubalis) na Ilha de Marajó, Pará - Silva, Jenevaldo B. [UNESP]; Lopes, Cinthia T.A.; Pinheiro, Cleyton P.; Lima, Danilo H.S.; Silva, Roberto S.L.; Fonseca, Adivaldo H.; Araújo, Flábio R.; Barbosa-Neto, José D. (FapUNIFESP (SciELO), 2013)
The aim of the study was to estimate the prevalence of Babesia bovis and Babesia bigemina in water buffaloes of the Marajó Island, State of Pará, Brazil. We used an indirectenzyme- linked immunosorbent assay (iELISA), with total antigen containing proteins outer surface, and polymerase chain reaction (qPCR), involving the use of SYBR Green based on amplification of a small fragment of the cytochrome b gene. The prevalence of positive animals in iELISA to B. bovis B. bigemina and mixed infection was 24.87% (199/800), 20.75% (166/800) and 18.75% (150/800), respectively. Using the PCR, the presence of B. bovis wasdetected in 15% (18/199) and B. bigemina in 16% (19/199) of animals, and of these, 58% (11/19) presented co-infected by the two agents. The results show a low prevalence of antibodies anti-B. bovis and anti-B. bigemina in water buffaloes from Marajó Island. However, it was observed that the agents of bovine babesiosis circulate in buffaloes, and these may act as reservoirs.
Molecular and serological prevalence of babesia bovis and babesia bigemina in water buffaloes (bubalus bubalis) on marajo island, state of pará, brazil
Keywords: Babesia bigemina; Babesia bovis; Bubalus bubalis; Buffaloes; ELISA; Marajó Island.; QPCR